2017
DOI: 10.1556/2050.2017.0001
|View full text |Cite
|
Sign up to set email alerts
|

All in the family: Attitudes towards cousin marriages among young dutch people from various ethnic groups

Abstract: This is an open-access article distributed under the terms of the Creative Commons AttributionNonCommercial 4.0 International License (https://creativecommons.org/licenses/by-nc/4.0/), which permits unrestricted use, distribution, and reproduction in any medium for non-commercial purposes, provided the original author and source are credited, a link to the CC License is provided, and changes -if any -are indicated.© Abstract. The present research examined attitudes towards cousin marriages among young people f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Consequently, women may be more sensitive to the potential disadvantages of cousin marriages than men. Indeed, in a study among young people from The Netherlands, women reported more negative attitudes towards cousin marriages than men did (Buunk 2017). We therefore expected similar sex differences in the present study.…”
Section: Sex Differencessupporting
confidence: 78%
See 4 more Smart Citations
“…Consequently, women may be more sensitive to the potential disadvantages of cousin marriages than men. Indeed, in a study among young people from The Netherlands, women reported more negative attitudes towards cousin marriages than men did (Buunk 2017). We therefore expected similar sex differences in the present study.…”
Section: Sex Differencessupporting
confidence: 78%
“…Overall, the young people in this Mexican sample tended to have somewhat less negative attitudes towards cousin marriage than the Mexican adults from the same region (Buunk and Hoben 2013), but their responses were similar to those of young Dutch people from various ethnic groups, except that in the present sample, religious reasons were a more important objection and marrying someone with the same values a more relevant consideration (Buunk 2017). Overall however, the present findings suggest that attitudes towards cousin marriages in such diverse countries as Mexico and The Netherlands-where the law does not prohibit cousin marriage-do not differ in major ways.…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations